2018
DOI: 10.2116/analsci.18p381
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive and Selective Detection of Mercury Ions in Aqueous Media Using an Oligonucleotide-functionalized Nanosensor and SERS Chip

Abstract: A surface-enhanced Raman scattering (SERS) platform for the selective trace analysis of Hg 2+ ions was reported, based on poly-thymine (T) aptamer/2-naphthalenethiol (2-NT)-modified gold nanoparticles (AuNPs), which was an oligonucleotide-functionalized nanosensor and SERS chip. 2-NT was used as a Raman reporter, and T aptamer could form a T-Hg 2+ -T structure with Hg 2+ ions making an SERS nanosensor absorbed to the SERS chip. The optimum concentrations of DNA and 2-NT were obtained. An average of 960 DNA mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…This nanosensor exhibits a LOD of 1.0 ppt (1.0 × 10 −12 g mL −1 ), which is much lower than the WHO's recommended drinking water level of 10.0 ppb. 85 Similarly, as illustrated in Scheme 4 , Sarfo and Sivanesan et al devised a SERS sensor by conjugating aminodibenzo-18-crown-6 with mercaptopropionic acid. The resulting crown ether derivative (TCE) self-assembled on the surface of the gold nanostructure of the substrate to form a distinct surface layer for Hg( ii ) ions.…”
Section: Nano-sensors As Potential Detection Approach For Mercury Ionsmentioning
confidence: 99%
“…This nanosensor exhibits a LOD of 1.0 ppt (1.0 × 10 −12 g mL −1 ), which is much lower than the WHO's recommended drinking water level of 10.0 ppb. 85 Similarly, as illustrated in Scheme 4 , Sarfo and Sivanesan et al devised a SERS sensor by conjugating aminodibenzo-18-crown-6 with mercaptopropionic acid. The resulting crown ether derivative (TCE) self-assembled on the surface of the gold nanostructure of the substrate to form a distinct surface layer for Hg( ii ) ions.…”
Section: Nano-sensors As Potential Detection Approach For Mercury Ionsmentioning
confidence: 99%
“…The repeatability and stability of the experiment are also an important parameter when performing SERS detection of ketamine. 26,27 Under the above-mentioned optimal detection conditions, the repeatability of SERS detection for ketamine aqueous solution at a concentration of 5 ppm was conducted, as demonstrated in Fig. 3(a).…”
Section: Preparation Of Silver Sol and Selection Of Aggregate Agentmentioning
confidence: 99%
“…Zou et al reported on a surface-enhanced Raman scattering (SERS) platform for the selective trace analysis of Hg 2+ based on poly-thymine (T) aptamer/2naphthalenethiol (2-NT)-modified Au nanoparticles. 7 T aptamer forms a T-Hg 2+ -T structure with Hg 2+ , and 2-NT was used as a Raman reporter. The detection limit was 1.0 ppt, far below the limit of 10.0 ppb for drinking water required by the WHO.…”
mentioning
confidence: 99%